Improving Fecal Immunochemical Testing Rates for Colon Cancer Screening in the Outpatient Setting. Issue 2 (February 2021) - Hussain, We'am; Aurand, William; Onuorah, Nneoma; Krstevski, Gabrielle; Markert, Ronald; Springer, Kerianne; Agrawal, Sangeeta
Abstract : Objectives: The amount of colorectal cancer (CRC) screening using the noninvasive fecal immunochemical test (FIT) at a federally qualified health center, Five Rivers Health Clinic (Dayton, Ohio), has been low historically. Our quality improvement (QI) project aimed to improve CRC screening adherence in eligible patients who opted for FIT. Methods: Three hundred ninety-two patients with FIT orders for CRC were screened during an 11-month period. The preintervention group (pre-I) was enrolled from December 1, 2018 to May 31, 2019, and the postintervention group (post-I) from June 1, 2019 to October 31, 2019. Three interventions were used: resident physicians trained during clinic meetings regarding FIT education for patients, posters displayed in patient rooms outlining the benefits of CRC screening, and standardized US mail reminder letters sent to FIT patients. Patient demographics and clinical variables were collected along with return rate. Results: The return rate for post-I was twice that of pre-I (74.4%, 95% confidence interval 64.6–82.3 vs 31.1, 95% confidence interval 26.2–36.6; P < 0.001). The pre-I/post-I groups did not differ on demographic and clinical characteristics, and, except for race, none of these variables was associated with returning the FIT screening card. Conclusions: The compliance rate for FIT completion and return more than doubled among our clinic patients after using a three-component QI intervention. Except for a difference in race, the lack of association between demographic and clinical characteristics with either pre-I/post-I group or return/no return of the FIT card leads us to conclude that our QI program for increasing FIT compliance is effective. Other settings where CRC screening is a prominent component of preventive care may benefit from adopting a similar QI intervention. Abstract : The authors' quality improvement project aimed to improve colorectal cancer screening adherence in eligible patients who opted for fecal immunochemical testing (FIT). Three interventions were used: resident physicians trained during clinic meetings regarding FIT education for patients; posters displayed in patient rooms outlining the benefits of colorectal cancer screening; and standardized US mail reminder letters sent to FIT patients. The return rate for post-I was twice that of pre-I.